Determinants of childhood diarrhea among under-five year old children in Nigeria: A population-based study using the 2013 demographic and health survey data - Berde, Anselm S.; Yalçın, Sıddıka Songül; Özcebe, Hilal; Üner, Sarp; Karadağ-Caman, Özge (The Turkish Journal of Pediatrics, 2018)
The study aims to identify socioeconomic, demographic, environmental and child baseline factors associated with Childhood Diarrhea (CD) among under-five year old children in Nigeria. We utilized cross-sectional data from the 2013 Nigerian Demographic and Health Survey (NDHS). The study covered 18,047 mother-baby pairs. The key outcome variable was CD. Chi-square tests and binary logistic regression were used to test for association between CD and related factors. The prevalence of CD was 12.6%. In the multivariate analysis, the following factors were significantly associated with increased risk of CD; younger mother`s age, household size of seven and above, unsafe disposal of child`s last fecal matter and younger child`s age. Also, children living in all geopolitical zones as compared to the South South geopolitical zone had significantly higher risk of CD. Interventions such as information, education and communication programs on hygiene and sanitation aimed at reducing CD in Nigeria should focus more on groups at risk for CD highlighted in our study.